ANALISA MENINGKATNYA PEMAKAIAN OLI PADA ENGINE C7 EXCAVATOR 320D CATERPILLAR MENGGUNAKAN 8 STEP TROUBLESHOOTING (STUDI KASUS PT. KASONGAN BUMI KENCANA) - Lintar Hariyandi; Qomariyatus Sholehah; Achmad Kusairi Samlawi (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2017)
Excavator 320D using C7 engine. Based on the problems that have occurred in the engine C7 in one company that is engaged in coal mining in which the number of engine problems that occur due to frequent loss of oil or increased oil consumption in the engine (High Oil Consumption), Using 8 Step troubleshooting with the goal knowing the cause of increased use of oil in the Engine C7 Caterpillar 320D Excavator and, Knowing the impact of rising oil consumption of the engine components Caterpillar 320D Excavator C7, and Knowing the cost of losses due to increased oil consumption in the Engine C7 Caterpillar 320D Excavator. After analysis 8 step troubleshooting is known to cause increased oil consumption is excessive because of the use of air cleaner is not in accordance with the OMM (Operational Manual Maintenance applicable, the impact of increased oil consumption which These conditions lead to premature wear on the components and the cost of repair to the engine that experienced high oil consumption amounted Rp.309.056.768